OF THE REPUBLIC OF KAZAKHSTAN ON INTERNATIONAL SECURITY IN COOPERATION SOME LEGAL ISSUES OF ENSURING (Journal of actual problems of jurisprudence, 2019)
This article includes the food security problems of Kazahstan in the context of international cooperation.